A latent profile analysis of aggression and prosocial behavior in relation to adolescent wellbeing - Lénia Carvalhais; Lénia Carvalhais; Paula Vagos (Frontiers in Psychology, 2025)
IntroductionAggressive and prosocial behaviors have often been addressed as opposing constructs, namely in their opposite association with subjective wellbeing. Alternatively, the Resource Control Theory assumes that individuals may resort to both aggressive and prosocial behaviors as strategic ways to obtain individual and social resources, which are particularly relevant in adolescence. This bistrategic use of social behaviors may be particularly noticeable when considering the overt and indirect forms of aggression but these forms have not been considered before in relation to prosociality.MethodThe current work explored profiles based on prosocial and aggressive behavior (i.e., relational, reputational and overt) and compared those profiles on different dimensions of subjective wellbeing. Participants were 350 students aged 11 to 18 years old (Mage = 13.40) attending the 7th through 9th school grades, of which 191 (54.6%) were female. They reported on the practice of overt aggression, relational aggression, reputational aggression, and prosocial behavior and their emotional, social, and psychological wellbeing.ResultsUsing latent profile analyses, typical and bistrategic profiles were found. Mean comparisons further showed that participants in these two profiles differed in all forms of aggressive behavior but not in the practice of prosocial behavior nor emotional, social, and psychological wellbeing, which might have been driven by prosociality.DiscussionWhen considering the forms of aggression in a community and age-diverse sample, adolescents seem resourceful in responding to their inter and intrapersonal developmental needs while maintaining their wellbeing. Promoting prosocial behavior as a valid alternative to aggression may have to be rooted in the intention with which these acts are practiced so that both are openly seen as ways of sustaining not only the others' but also one's own welfare.